A geometric morphometrics and genetics characterization of Vanessa carye in an extreme elevational gradient in the Chilean Altiplano - Escobar-Suárez, Scott; Villalobos-Leiva, Amado; Fabres, Alejandra; Órdenes-Clavería, Rodrigo; Cruz-Jofré, Franco; Laroze, David; Correa, Margarita; Valladares, Moisés A.; Cáceres, Juan Sebastián D.; Benítez, Hugo A. (Zoologischer Anzeiger, 2023)
The Western Painted Lady butterfly, Vanessa carye (Hüber, 1812), in addition to pre-senting an extensive distribution in South America, has been observed flying in the Chilean Alti-plano from the coast to the highlands, from 0 to 5200 m.a.s.l. and it is suggested that could be a migratory insect. Some animal species move from one place to another by migration searching for favorable conditions. Wings of flying migratory animals are the principal trait involved in move-ment, and their shape has been documented to change between migratory and non-migratory species or populations. In this sense, little is known about the adaptations of butterflies to elevational gradients, so the V. carye's wide latitudinal and altitudinal range coupled with the different climatic conditions makes this species an interesting subject for adaptation studies. This research studies V. carye at different elevational ranges in extreme environments at the Chilean Altiplano and Atacama Desert to determine the presence of morphotypes through geometric morphometrics associated with altitudinal patterns, and to determine the genetic diversity and population structure of this species by using COI molecular marker. Subtle morphometric changes between populations were found, so two morphometric lineages were defined: a “coastal” lineage with more elongated wings and an “altiplano” lineage with more rounded wings. Nevertheless, low genetic diversity and no genetic structure associated to these morphological differences were found. Understanding the processes underlying the wing shape of V. carye morphological adaptations will help to understand its natural history. Results here may be a first approach of evidence to answer the question “Is this butterfly a migratory species?”